Three new species of boesenbergia (zingiberaceae) from Sabah, Malaysia - Nyee Fan Lam; Halijah Ibrahim; Yen Yen Sam; Rozainah Mohammad Zakaria; Axel Dalberg Poulsen (Pensoft Publishers, 2024)
Three new species of Boesenbergia, B. bosuangii sp. nov., B. ganaensis sp. nov. and B. gokusingii sp. nov. were discovered in Sabah, Malaysia. Boesenbergia bosuangii is similar to B. stenophylla R.M.Sm. in the narrowly ovate lamina but differs in the shape of the bract and the calyx. Boesenbergia ganaensis is closely allied to B. burttiana R.M.Sm. but differs in the absence of a ligule, the longer petiole, the obtuse leaf base, the acute leaf apex, the bilobed calyx and the anther dehiscing by pores. Finally, B. gokusingii is similar to B. variegata R.M.Sm., by the single leafy shoot but differs in having an unequal, ovate lamina, a cordate leaf base, an acute leaf apex and the anther dehiscing by pores. The three new species are described and illustrated in detail. With the addition of these new species, there are in total 13 species with one variety in Sabah.